ANALISIS PERUBAHAN WAKTU SALAT AKIBAT REVOLUSI BUMI PERSPEKTIF HUKUM KEPLER 1 DAN ILMU FALAK - Maulana, Muh. Ardi; Mustafa, Adriana (HISABUNA: Jurnal Ilmu Falak, 2025)
Abstract This research presents three problem formulations, namely: First, what is the urgency of prayer times and its changes in Islam? Second, what are the implications of the Earth's revolution on prayer times? Third, how is the analysis of changes in prayer times due to the Earth's revolution from the perspective of Kepler's 1st law and astronomy? This type of research is qualitative using descriptive analysis methods. The authors specifically use two approaches. An astronomical approach that is directly related to the phenomena of the universe, such as the planets and their movements, and the Sun. The syar'i approach is directly related to prayer times based on the Koran and Al Hadith. Data was obtained through library research by quoting and analyzing using content analysis on literature relevant to the problem being discussed, then reviewing and concluding. The results of this research show that: first, the urgency of prayer times and their changes in Islam emphasizes the importance of observance of worship times, awareness of possible time changes and readiness to adapt religious practices to the specified times. Second, the way the Earth evolves affects the time periods of day and night, which determine prayer times such as dawn and dusk. Variations in the distance between the Earth and the Sun in one revolution cause changes in prayer times throughout the day during the year. Third, a deep understanding of the principles of astronomy, including Kepler's law 1 and astronomy, is very important in determining prayer times in accordance with religious principles. This shows the importance of integration between science and religious knowledge in daily practice. The implication of this research is to explore Kepler's law 1 in determining changes in prayer times, including the position of the Earth and the Sun in daily worship practices throughout the year. It is important to pay attention to and observe some of the signs of His greatness, namely the Sun and the Earth, to know the beginning of prayer times.